Low Pre-Conception Health Among Iraqi College Women Linked to Age and Socioeconomic Status: Kesehatan Pra-Konsepsi yang Rendah di Kalangan Perempuan Irak Berkaitan dengan Usia dan Status Sosial Ekonomi - Nawres jameel Arief; Prof dr Arkan bahlol Naji (Academia Open, 2024)
This study explores pre-conception health behaviors among female college students at the University of Baghdad, highlighting a critical gap in non-Western contexts. Conducted from October 2023 to March 2024 with 144 participants, the cross-sectional study assessed pre-pregnancy health behaviors using a validated 5-point Likert scale. Results showed that 74.4% of students exhibited low pre-conception health behaviors, with significant predictors being age (p = 0.008), academic grade (p = 0.041), and socioeconomic status (p = 0.035). The average participant age was 20.63 years, with most in their first academic year and living with parents. The findings emphasize the need for targeted interventions and educational programs to improve pre-pregnancy health awareness and behaviors in this demographic. Highlights: High Prevalence: 74.4% exhibited low pre-conception health behaviors. Influential Factors: Age, grade, and socioeconomic status significantly impacted behaviors. Intervention Needed: Educational programs essential for improving pre-conception health awareness. Keywords: pre-conception health, female college students, predictive factors, socioeconomic status, health behaviors